Fontes energéticas para recria de novilhos holandeses mantidos em pastagens de aruana sobresemeada com aveia branca e azevém durante o inverno - Martinello, Clederson (2014)
The aim of this study was to evaluate the effect of energy sources in isonitrogenous diets on average daily gain (ADG), weight gain per area (GPA) in steers grazing Aruana grass (Panicum maximum Jacq. Cv. Aruana ) sown on with oat (Avena sativa L.) and ryegrass (Lolium multiflorum Lam.). The study was conducted at UNEP Cattle Cutting the Federal Technological University of Paraná, UTFPR - Campus Dois Vizinhos. The seeding rate used was 50 kg / ha of seed oat. Treatments were supplementation of 1.5% of body weight of ground corn (GC), wheat bran (WB), or soybean hulls (CS). The experimental design was completely randomized with two replications. 18 Holstein calves were used, not castrated, with 07 months of age and initial weight of 140 kg evaluating the average daily gain per hectare. Treatments with energy sources, soybean hulls, wheat bran and ground corn as an energy source in the diets isonitrogenous Holstein calves presented similar performances obtaining values of average daily gain 1.09 / ha, 0.95 / and 1.05 ha / ha, respectively, no differences were detected.